Clonidine and phenylephrine injected into the lateral preoptic area reduce water intake in dehydrated rats - Callera, João Carlos [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Saad, Wilson Abrão [UNESP] (Elsevier B.V., 1993)
In the present study, we investigated the effect of phenylephrine and clonidine (α1- and α2-adrenoceptor agonists, respectively) injected into the lateral preoptic area (LPOA) on the water intake induced by water deprivation in rats. In addition, the effects of prior injections of prazosin and yohimbine (α1- and α2-adrenoceptor antagonists, respectively) into the LPOA on the antidipsogenic action of phenylephrine and clonidine were investigated. After 30 h of water deprivation, the water intake of rats in a control experiment (saline injection) was 10.5 ± 0.8 ml/h. Injection of clonidine (5, 10, 20, and 40 nmol) into the LPOA reduced water intake to 6.3 ± 0.9, 4.9 ± 0.8, 3.6 ± 1.0, and 2.2 ± 0.7 ml/h, respectively. Similar reductions occurred after injection of 80 and 160 nmol phenylephrine into the LPOA (6.2 ± 1.6 and 4.8 ± 1.3 ml/h, respectively). Pretreatment with prazosin (40 nmol) abolished the antidipsogenic action of an 80-nmol dose of phenylephrine (11.3 ± 1.1 ml/h) and reduced the effect of a 20-nmol dose of clonidine (7.4 ± 1.4 ml/h). Yohimbine (20, 40, and 80 nmol), previously injected, produced no significant changes in the effects of either phenylephrine or clonidine. The present results show that phenylephrine and clonidine injected into the LPOA induce an antidipsogenic effect in water-deprived rat. They also suggest an involvement of α1-adrenoceptors in this effect. A possible participation of imidazole receptors in the effect of clonidine should also be taken into account. © 1993.
Keywords: α-Adrenoceptors; Clonidine; Preoptic area; Thirst; Water intake; Alpha 1 adrenergic receptor; Alpha 1 adrenergic receptor blocking agent; Alpha 1 adrenergic receptor stimulating agent; Alpha 2 adrenergic receptor blocking agent; Alpha 2 adrenergic receptor stimulating agent; Clonidine; Phenylephrine; Prazosin; Yohimbine; Animal experiment; Animal tissue; Controlled study; Dehydration; Drug antagonism; Fluid intake; Histology; Intracerebral drug administration; Male; Nonhuman; Preoptic area; Priority journal; Rat; Thirst; Adrenergic alpha-Agonists; Animal; Dehydration; Drinking Behavior; Injections; Male; Phenylephrine; Prazosin; Preoptic Area; Rats; Receptors, Adrenergic, alpha-1; Receptors, Adrenergic, alpha-2; Support, Non-U.S. Gov't; Yohimbine